Oat grain yield under nitrogen uses in an eucalyptus intercropping system in Subtropical Brazil - Deiss, Leonardo; Moraes, Anibal; Pelissari, Adelino; Silva, Vanderley; Andreolla, Veruschka (Revista Ciência Agronômica, 2016)
Agronomic practices adequacy plays a key role in the integrated crop-livestock systems development. The objective of this study was to determine how the phytomass accumulation, yield compounds and oat (Avena sativa L. cv. IPR 126) yield were influenced by nitrogen levels (12 and 80 kg N ha-1) at five equidistant positions between two adjacent eucalyptus (Eucalyptus dunnii Maiden) double line tracks [20 m (4 m x 3 m)] in intercropping system (IS) and traditional no-till agriculture (without trees) in subtropical Brazil. The experiment was conducted in a split-block in a randomized block design with four replicates. At the end of the oat cycle, there was compensation for the lower spikelets per panicle number by the greater grain per spikelet number, and for higher harvest indexes where oat accumulated less phytomass in environments with high interspecific interaction. The nitrogen levels increase the oat yield differently at positions relative to the trees in the IS. Therefore different nitrogen levels should be used at those distances to increase nitrogen use efficiency inside IS in subtropical Brazil.